Sequence-Defined Oligothioetheramides - Porel, Mintu; Brown, Joseph S.; Alabi, Christopher A. (Synlett, 2015)
The importance of sequence-defined polymers is evident in highly developed biological systems. As such, their synthetic de novo production with similar macromolecular diversity, efficiency, and speed has been the focus of considerable research. In this brief review, the rationale behind the new synthesis of sequence-defined oligothioetheramides (oligoTEAs) will be placed in context with the accepted methods of peptide and peptoid synthesis, where all methods notably utilize chemical orthogonality in their design. Along with the conceptual design, we will discuss the assembly of oligoTEAs by highlighting the solution-phase kinetics of each orthogonal reaction, the liquid-phase fluorous purification methodology, a proof-of-principle synthesis, and the assembly of a full-length oligomer. Overall, the success of oligoTEAs stems from the rapid orthogonal chemical reactions at each end of the unique N-allyl-N-acrylamide monomer. OligoTEAs seek to contribute and advance the field of sequence-defined polymers by providing additional structural diversity to fundamentally study sequence-structure-function relationships for both material science and biological applications.1 Introduction2 Supported Synthesis via Orthogonal Chemistries3 Conceptual Design of OligoTEA Assembly4 Proof-of-Principle5 Synthesis and Characterization of OligoTEAs6 Conclusion
Keywords: oligothioetheramide; sequence-defined; thiol-ene; orthogonal; polymer